Integrating Social-Emotional and Academic Development in Teachers' Approaches to Educating Students. (October 2019) - Cross Francis, Dionne; Liu, Jinqing; Bharaj, Pavneet Kaur; Eker, Ayfer
Student success should incorporate not only academic achievement, but also the skills and competence to identify and effectively pursue personal life goals. However, success has become narrowly defined by test scores, which minimizes students' opportunities for growth and development. Research findings show the interrelatedness of social, emotional, and cognitive dimensions of learning and how these dimensions shape positive student outcomes. In this article, we discuss how schools can integrate social, emotional, and academic development in optimizing student learning. Foregrounding teachers, the engines that drive the educational practices within schools, we describe their role in shaping student outcomes and identify the essential knowledge and skills needed to create academically and emotionally enriched spaces for students. We discuss the gaps in current teacher education and professional development (PD) programs that result in teachers being ill-prepared for the realities of the classroom. Finally, policy implications for teacher education, PD, and school reorganization are discussed.